KNOWLEDGE, ATTITUDE AND PRACTICE ABOUT PRIMARY EYE CARE AMONG MEDICALSTUDENTS OF UNIVERSITY OF LAHORE (The Research of Medical Science Review, 2024)
Background: Primary eye care is essential for attaining standard health. So, healthcare professionals and specially students must have a firm grip on primary eye care. The management of primary eye problems is not only the domain of the ophthalmology department, but general eyephysicians can also treat primary eye problems. In this context,there is a need to assess the knowledge, attitude, and practice of medical students about primary eye care.Objective: The fundamental objective of the research is to assess the knowledge, attitude,and practice about primary eye care among medical students of University of Lahore.Methodology: The cross-sectional study design was used in the research. The interviews of178 participants were conducted using the questionnaire. The questionnaire consisted of 24questions and had three sections. Every section consisted of 8 questions which represented knowledge-based, attitude-based, and practice-based questions. The questions were close ended, so the participant’s responses were quantified in the research. For this purpose, the excel sheet was used for arranging the data, whereas SPSS 24.0 was used for generating the results.Results: The medical students participated in the research were 178 of which 92 (51.7%) of the students were males, whereas 86 (48.3%) students were females. The analysis showed that 76% of medical students had good knowledge while 24% of medical students had poor knowledge. About 73% of medical students had good attitude while 27% of medical studentshad poor attitude. However, only 58% of medical students had good practice while 42% of medical students had poor practice towards primary eye care.Conclusion: It is concluded that the medical students have enough knowledge, appropriateattitudebut require necessary practice about primary eye care.